A qualitative analysis of the COVID-19 vaccination rollout in Lagos, Nigeria: Client and provider perspectives on the plan, the process and the progress - Oluchi Kanma-Okafor; Yetunde Odusolu; Akin Abayomi; Faisal Shuaib; Moji Adeyeye; Ibrahim Mustapha; Segun Ogboye; Dayo Lajide; Hussein Abdur-Razzaq; Ukamaka Okafor; Uchenna Elemuwa; Akin Osibogun (Public Library of Science (PLoS), 2022)
Mass vaccination has proven useful in the control of COVID-19, though vaccine rollout has met major challenges. The learning curve of this process has been valuable. This qualitative study aimed to assess the plan, the process and the progress of the COVID-19 vaccination rollout in Lagos, Nigeria. This study was conducted at vaccination centers in eight of the 20 Local Government Areas in Lagos State from May to July 2021 among healthcare administrators, health workers and vaccine recipients. Data were collected by conducting three key informant interviews, 24 in-depth interviews and eight focus group discussions to explore the vaccination experiences of participants and the challenges facing the vaccination plan and process. The interviews and discussions were recorded, transcribed verbatim and analyzed using the thematic approach. The four-phased plan for the vaccine rollout was clear to all the key informants because the vaccination process was preceded by training. The process was strengthened by the electronic registration system, though riddled by the frequently unstable electronic and internet data capturing. This was mitigated by a stopgap manual registration and recording of client details. Challenges in the logistics of maintaining supplies of the disposable materials required for the vaccination process were overcome by the creativity of the health professionals. Vaccine hesitancy, fueled by misinformation, myths and misconceptions about the vaccine and its side effects, played a huge role in the community response. The reported vaccine side effects were mild; fever, headaches, pain at the injection site, excessive eating and sleepiness. Though the COVID-19 vaccination process appeared to have largely made progress, the future of vaccination in Nigeria is predicated upon a bottom-up approach to programmatic planning, health education and local vaccine production. Collaborations such as public-private partnerships have the potential of boosting vaccine provision for Nigeria's large population to ensure equitable access to vaccines.